Penyelesaian Sengketa Bisnis Syariah: Penguatan Regulasi untuk Kepastian Hukum Surat Berharga Syariah Negara di Indonesia - Mulazid, Ade Sofyan (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2021)
This study aims to determine and analyze the balance of disputes over Sharia Securities (SBSN) as an effort to ensure legal and other regulations that provide opportunities for sharia economic development, especially SBSN. This study uses a normative juridical method with a qualitative approach. The results of the study show that the Supreme Court Regulation Number 14 of 2016 concerning Procedures for Settlement of Sharia Economic Cases and Supreme Court Regulation Number 2 of 2015 concerning Procedures for Simple Lawsuits strongly support the regulation of SBSN legal certainty in Indonesia. Apart from litigation, SBSN disputes can also be pursued through non-litigation channels according to Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution.